2022
DOI: 10.1111/jam.15511
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus altitudinis HNH7 and Bacillus velezensis HNH9 promote plant growth through upregulation of growth-promoting genes in upland cotton

Abstract: Aims:The potential of endophytic Bacillus strains to improve plant growth and yield was evaluated. Methods and results: Endophytic Bacillus altitudinis HNH7 and Bacillus velezensisHNH9 were evaluated for their growth-promoting traits. In an in vitro plate assay, HNH7 and HNH9 exhibited proteolytic, amylolytic, lipolytic and cellulolytic activity.HNH7 and HNH9 were able to solubilize iron by producing siderophores but were unable to solubilize insoluble phosphate. PCR confirmed the presence of four growthpromot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…LC–MS successfully detected the presence of surfactin, iturin, fengycin, bacillaene, bacillibactin, plantazolicin, and bacilysin in CHGP12. In a similar report LPs produced by B. altitudinis HNH7 and B. velezensis HNH9 were detected through LC–MS, and it was concluded that the significantly high inhibitory potential of these strains was due to the presence of LPs 20 . According to previous reports, the simultaneous detection and production of antimicrobial LPs and their antifungal activities are correlated 46 .…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…LC–MS successfully detected the presence of surfactin, iturin, fengycin, bacillaene, bacillibactin, plantazolicin, and bacilysin in CHGP12. In a similar report LPs produced by B. altitudinis HNH7 and B. velezensis HNH9 were detected through LC–MS, and it was concluded that the significantly high inhibitory potential of these strains was due to the presence of LPs 20 . According to previous reports, the simultaneous detection and production of antimicrobial LPs and their antifungal activities are correlated 46 .…”
Section: Discussionmentioning
confidence: 60%
“…In addition to hydrolytic enzymes, CHGP12 also showed the potential to produce siderophores, IAA and GA. In previous reports Bacillus species have been reported to produce hydrolytic enzymes, siderophores, IAA, and GA 20,52 . Several previous reports have proved the direct effect of siderophores on the growth promotion of plants 20,53,54 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…and Streptomyces spp. ( Kataoka et al, 2021 ), Rhizobium pusense MB-17a ( Chaudhary et al, 2021 ), P. liquidambaris ( Zhou et al, 2022 ), Bacillus altitudinis ( Zhang et al, 2021 ; Hasan et al, 2022 ), and P. giganteum ( Yankey et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%